Quantitative Fire Risk Assessment of Crude Oil Tank at Company A - Andralisa Febriani; Fatma Lestari (Jurnal Indonesia Sosial Sains, 2024)
The oil and gas industry has a high risk of losses due to fire. There have been several fire incidents in the oil industry involving fires in crude oil tanks. The objective of this research is to assess the level of fire risk in Crude Oil Tank T32 at Company. The research method used is to analyze the frequency of fire occurrences using event tree analysis and modeling the consequences of fires using ALOHA software. After conducting frequency analysis and consequence modeling, individual risk and social risk are calculated. Results: Based on the results of consequence modeling, the furthest distance for heat radiation with a 100% risk of death is 84 meters. The largest risk calculation result is in the leaky tank scenario with a hole size of 100 mm with an individual risk value of 1,84 x 10-8 and a social risk value of 3,13 x 10-7. The results of the T32 tank fire risk assessment at Company A's oil collection tank facility show that individual and social risks are still within the acceptable risk category according to the UK HSE Risk Acceptance Criteria. Even though the risk of a fire incident is still within acceptable limits, risk control efforts still need to be carried out so that the risk remains within acceptable tolerance limits